The Underrepresentation and the Disinterest of Malay Women in Nursing in the Early Post-Colonial Malaysia (1957-1977): A Cultural Perspective - Saidun, Salilah (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
Modern nursing started in Malaysia during the colonial rule and with embedded colonial values. During the first two decades of post-independent Malaysia, the Malays were a minority in the nursing workforce despite being the majority population. This study examines the issue of this paradoxical underrepresentation of Malay women from the lens of Malay culture during this period. Document analysis was conducted on relevant annual reports, official letters, minute papers, newspaper articles and parliamentary debates official reports between 1957 and 1977. The findings suggest that the underrepresentation of the Malays in nursing was predominantly due to the disinterest of Malay women to become nurses due to the discordance between the Malay culture and various aspects of nursing. This article highlights the importance of a culturally sensitive work environment in promoting inclusivity for the diverse members of the society. Keyword: Nursing, Malay women, post-colonial, inclusivity, diversity